The Linguistics of Name Translation: Preferred Personal and Business Names in English, Korean, and Chinese. (2nd April 2020) - Kim, Jong-mi
Abstract : This research examines personal and business names and their translations among typologically contrastive languages: English, Korean, and Chinese. A linguistic framework is proposed that predicts and tests whether and how ideal translations will be based on sound or meaning, as defined by the phonetic or semantic features of the given orthography. Two separate surveys (online in the US and onsite in Korea) were taken about preferred translations of names from and to the three languages. The linguistic prediction was borne out by the survey results: sound translation is preferred from and to English, meaning translation from and to Chinese, and preference is mixed from and to Korean. An additional finding was that translation preference was sound-based for personal names but meaning-based for business names. The full list of 118 original names and 302 translation choices in the three languages investigated in this study is provided in the appendix.